14 Podcasting as an Extension Tool: Limitations and Opportunities. (8th March 2022) - Bennett, Samantha P; Mulvaney, Donald
Abstract: Current challenges for Extension include decreased travel budgets and prompts for increased consideration of the use of online delivery tools for educational content programming with the goal of expanding stakeholder development and engagement. Podcasts (PCs) are audio and/or video content that can be played on computers and handheld devices through the use of Really Simple Syndication (RSS) technology. PCs are communication modalities with perceived high potential for incorporation into the pedagogical toolbox for the creation of an online resource repository and strategic virtual public outreach programming. PCs are audience focused forms of content that provide information to stakeholders in a way that allows for them to listen to what they want, when they want, where they want, and how they want. The Ag Communication Research Group distributed Qualtrics surveys to Alabama Cooperative Extension System (ACES) personnel across the state. Data collected enabled the examination of ACES personnel perspectives towards PCs and the current status of PC use for their work. Survey results indicate diverse views, varied levels of PC understanding, plans for adoption, and perceived barriers for use of PCs in Extension. Of participants, 62.5% currently listen to podcasts themselves and only 13.6% have participated in the creation or production of a PC before. When asked if participants have considered creating a PC for ACES 60.2% responded no, 17% responded maybe, 29.1% said yes, and only 4.5% responded that they already have created a PC or are in the process of creating one. In addition, we also report on methods for developing an Extension-oriented PC series, identify salient points for educators interested in developing a PC series, and explore the potential value of PCs as a vibrant Extension education tool to communicate curated, trusted, and relevant information.